1984
DOI: 10.1212/wnl.34.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury, edema, and vascular permeability changes induced by oxygen‐derived free radicals

Abstract: We studied the cerebral effects of oxygen-derived free radicals generated from the xanthine oxidase/hypoxanthine/ADP-Fe3+ system. Xanthine oxidase/hypoxanthine/ADP-Fe3+ solution (0.1 ml) was infused into caudate putamen, and brain was frozen rapidly in situ. Brain water and sodium content increased concomitant with decreased potassium content at 24 hours and 48 hours after the infusion. The degree of brain edema and injury depended on the dose of xanthine oxidase. Spongy neuropil and neuronal cytoplasmic vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
0
3

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(131 citation statements)
references
References 0 publications
2
126
0
3
Order By: Relevance
“…Experimental studies indicate that hyperglycaemia may increase brain oedema [12], inflammatory reaction [13], free radical injury [14] and excitotoxic or apoptotic cell death after stroke [15], but these results have not yet been demonstrated in humans to our knowledge. Although several studies have described possible effects of hyperglycaemia in ICH patients [4,5,[16][17][18][19][20][21], these studies used either small populations [5,16,17,19] or long enrolment periods [4].…”
Section: Discussionmentioning
confidence: 95%
“…Experimental studies indicate that hyperglycaemia may increase brain oedema [12], inflammatory reaction [13], free radical injury [14] and excitotoxic or apoptotic cell death after stroke [15], but these results have not yet been demonstrated in humans to our knowledge. Although several studies have described possible effects of hyperglycaemia in ICH patients [4,5,[16][17][18][19][20][21], these studies used either small populations [5,16,17,19] or long enrolment periods [4].…”
Section: Discussionmentioning
confidence: 95%
“…McAllister et al [21] observed an association between the maximal inflammation in CSF and the time of death in rabbits with experimental pneumococcal meningitis. Extensive work by Fishman et al [23], Chan and Fishman [24], and Chan et al [25] has implicated granulocytes as an important factor in development of brain edema. Both arachidonic acid and other free polyunsaturated fatty acids [38][39][40], which represent major constituents of the granulocytic cell wall and are found in high concentrations in pus, as well as oxygen-derived free radicals [25,41] appear to be involved in the generation of brain edema in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies the time of death is associated with maximal inflammation in the subarachnoidal space [21], and one study suggested that neutropenic dogs with pneumococcal meningitis may survive longer than animals with a normal inflammatory reaction in the CSF [22]. Fishman et al [23], Chan and Fishman [24], and Chan et al [25] have demonstrated that products of leukocytes, such as polyunsaturated fatty acids and oxygen-free radicals, can induce brain edema, increased lactate production, and energy depletion in cortical brain slices of rats. However, the role of leukocytes in the mediation of brain edema during bacterial meningitis has not been examined.…”
mentioning
confidence: 99%
“…Because the vascular endothelium plays an important role in blood-brain barrier (BBB) maintenance as well as to responsiveness to vasoactive substances (Faraci and Heistad, 1998), the effects of trauma and ischemia on endothelial function is currently a critical area of investigation (del Zoppo and Mabuchi, 2003). Increased vascular permeability is observed in many models of brain ischemia (Chan et al, 1984;del Zoppo, 1997;Hatashita and Hoff, 1990). Acute alterations in BBB are observed during early periods of postischemic reperfusion (Yang and Betz, 1994) or embolic stroke (Dietrich et al, 1988).…”
Section: Vascular Perturbationsmentioning
confidence: 99%